2011
DOI: 10.1007/s00417-011-1722-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological findings and predisposing risk factors in corneal ulcers

Abstract: The bacterial spectrum is changing. The most effective drugs are chloramphenicol and fusidic acid, followed by ciprofloxacin. Specific systemic and local predisposing factors promote the risk of bacterial keratitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 19 publications
2
20
1
2
Order By: Relevance
“…The majority of the samples were taken from females (47 women and 26 men). Fifty two (64.15%) cultures were positive for bacteria (53.6% (22) in CU and 75% (30) in CL). A single bacteria was isolated in 27 of the 52 (51.9%) positive cultures and in the remaining 25 (48%) 2-4 bacteria were found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the samples were taken from females (47 women and 26 men). Fifty two (64.15%) cultures were positive for bacteria (53.6% (22) in CU and 75% (30) in CL). A single bacteria was isolated in 27 of the 52 (51.9%) positive cultures and in the remaining 25 (48%) 2-4 bacteria were found.…”
Section: Resultsmentioning
confidence: 99%
“…For the remaining Gram-bacteria quinolones and Ceftazidime were sensitive while Gentamicin was very resistant. Fortunately, Chloramphenicol revealed to be sensitive for P aeruginosa and Serratia [21][22]. Other bacteria, such as A Xyloxosidans found only in CL multi microbial cultures and not in CU cultures, were very resistant to classic antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 One isolate was found in only 7 culture-positive cases (64%), while multiple bacterial species were found in 4 (36%). No bacterial growth was detected in 42.1% of cases, but all our patients showed clinical features consistent with the diagnosis of bacterial keratitis and a good response to antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This finding seems in contrast with the majority of previous studies, where gram-positive infections, mostly Staphylococcus species, were found to be prevalent. 2,12,15 Nevertheless, it is of note that Pseudomonas aeruginosa is the most frequent isolated agent in contact lens-related ulcers, while gram-positive bacteria were more strongly associated with ocular surface diseases and corneal traumas. 2,16 This might be because Pseudomonas aeruginosa is a water-borne strain that can adhere to and colonize lens materials during wearing.…”
Section: Discussionmentioning
confidence: 99%
“…Other reports have listed P. aeruginosa and Staphylococcus species as the commonest bacterial organisms. 14,15,[19][20][21][22] Staphylococcus species were relatively rare in this study, and no methicillin-resistant S. aureus (MRSA) or methicillin-resistant S. epidermidis (MRSE) strains were identified. It is likely that the difference in distribution of organisms between South India and other geographic locations has to do with geography and climactic factors.…”
Section: Discussionmentioning
confidence: 99%